THE DEMAND FOR VIDEO CONTENT AMONG STUDENT YOUTH IN MODERN SOCIETY - Ekaterina V. Baranova; Yulia R. Guro-Frolova; Elena G. Sokolova (Russian Studies in Culture and Society)
Background. The article is devoted the topical issue of the impact of digital transformation processes in all spheres of human activity on the choice of means of personal and professional formation and development among student youth. The issue study was conducted by the authors in the form of a sociological experiment on the basis of the Volga State University of Water Transport in Nizhny Novgorod (hereinafter referred to as the VSUWT). The subject of the study is video content produced in Russia and abroad.